A Critique of Aaron Rock Singer's Understanding of Islam - Wulansari, Intan; Rasyid, Daud; Nazih, Abdullah Ghulam; Nurani, Dewi; Savitaningrum, Retno Kartini (Fakultas Agama Islam Universitas Islam As Syafi'iyah, 2025)
This paper critically examines the understanding of Aaron Rock-Singer, a contemporary Western academic in the field of modern Islamic studies, especially related to Islamism and revivalism in the Middle East. His works highlight the role of media, state, and daily practices in shaping Muslim religious authority and identity, especially in the context of modern Egypt. Using a social history approach and discursive theory, Rock-Singer attempts to reconstruct how Islam is practiced in the public sphere. However, this approach has been criticized by various groups, especially Muslim academics and postcolonial thinkers. The criticism is directed at Rock-Singer's tendency to ignore the spiritual, normative and epistemological dimensions of Islamic religious experience, as well as his reliance on the secular-liberal framework of analysis typical of Western academia. This paper aims to comprehensively evaluate Rock-Singer's understanding by addressing methodological and epistemological weaknesses from an internal Islamic perspective. It emphasizes the need for a more dialogical approach between Islamic intellectual traditions and Western academic studies so that the study of Islam does not merely become an object of outside study, but part of an inclusive global intellectual conversation.